Bing Maps: aerofotointerpretazione archeologica online. La visione panoramica "made in Microsoft” - Mastroianni, Davide (Archeomatica, 2014)
In the last years, the aerial archaeology confirmed the importance and the potentiality of aerial photography in the study of landscape that already was realized by Giacomo Boni, Franz Stolze and O.G.S. Crawford between the late nineteenth and the early twentieth century. Aerial photography is today a tool used in numerous fields: from geology to civil engineering, from the study of the environment to the identification of pollution sources, from architecture to archeology; in fact it is becoming a valid and indispensable tool for the study of the ancient topography. In this last field, the aerial photograph is really important if it is used as instrument of knowledge and research. The aerial view is sure the most useful tool for observe the modern landscape and all evidence or "marks” that would be unintelligible if they are observed from the ground. The great diffusion of internet has made possible the creation of catalogues that allow consulting maps, orthophotos, aerial and oblique images online; the Italian regions have decided to publish all data on internet with the creation of websites (WebGIS). However, it is possible to encounter serious difficulties in finding the photographic material because of high costs and long times, but thanks to the use of Bing Maps, a web mapping service of Microsoftâ„¢, it is possible to break down such restrictions. Bing Maps has high resolution oblique photographs, so called "Bird's Eye”, that allow to realize a free virtual aerial survey thanks to combined use of aerial and oblique images. This approach has been used to observe the modern landscape of Veio obtaining new archaeological useful data, without cost, for the reconstruction and update of ancient topography of Etruscan town.